Moving images making movies, understanding media - Casinghino, Carl (Clifton Park, N.Y. Delmar Cengage Learning, 2011)
"Fundamentals of movie creation and production." -- Back cover.
DVD includes award-winning short films.
Keywords: Motion pictures -- Production and direction; Motion picture authorship